Peran Ormas Bang Japar dalam Meningkatkan Jumlah Suara Fahira Idris pada Pemilihan DPD Tahun 2024 - Nur Syahbani, Alma; Rahmawati, Restu (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2025)
This study examines the role of the mass base in Fahira Idris' victory in the 2024 election. The rationale for this research stems from Fahira Idris's consistent victories in the three election periods she participated in. The theory used is the patron-client theory. The results show that the four indicators analyzed through the electoral and non-electoral participation approaches are proven to be interconnected and form a strong foundation for Fahira's relationship with Bang Japar. The imbalance of power is evident in Fahira's position as a provider of resources and political access. Personal ties are built through informal communication and symbolic attention that foster emotional loyalty. Dependence is evident in access to Fahira's programs and political support that Bang Japar utilizes. The reciprocal relationship is adaptive and pragmatic, but remains based on social loyalty norms that strengthen the stability of the relationship